2007
DOI: 10.2319/0003-3219(2007)077[0471:orfftd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Risk Factors for Temporomandibular Disorders

Abstract: Absence of bilateral canine guidance on lateral excursion and particularly Angle Class II malocclusion were considered important risk indicators for the development of TMD in this investigation, even when some sociodemographic factors were considered as effect modifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
4
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 26 publications
1
45
4
3
Order By: Relevance
“…We observed that the mean depression score was significantly higher in the TMD group than in the control group, in agreement with previous studies [32,33]. Elevated levels of depression have been repeatedly observed in TMD subjects [6,11,18,24,25,38].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the mean depression score was significantly higher in the TMD group than in the control group, in agreement with previous studies [32,33]. Elevated levels of depression have been repeatedly observed in TMD subjects [6,11,18,24,25,38].…”
Section: Discussionsupporting
confidence: 93%
“…However, Caio et al . did not find significant differences between TMD and non‐pain groups on the occlusal variables like overbite, overjet, etc.…”
Section: Introductionmentioning
confidence: 74%
“…Reasons for exclusion were described in Table . Search expansion strategies allowed including four additional papers, thus accounting for a total of 25 papers included in the review .…”
Section: Resultsmentioning
confidence: 99%